Manajemen SDM dalam Penanganan Stunting di Wilayah Kerja Dinas Pengendalian Penduduk, Keluarga Berencana, Pemberdayaan Perempuan dan Perlindungan Anak Kabupaten Paser - Istiqomah Istiqomah; Karlina Karlina; Nuriyah Nuriyah; Ainun Ainun; Rusmiati Rusmiati; Amir Hamzah (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2026)
Stunting remains a significant public health challenge in Indonesia, including in Paser Regency, East Kalimantan. Effective human resource (HR) management among community cadres is a critical factor in stunting prevention and intervention programs. This community service activity aimed to enhance the knowledge and skills of 33 Stunting Companion Cadres under the auspices of the Office of Population Control, Family Planning, Women's Empowerment and Child Protection (DPPKBPPPA) of Paser Regency through counseling and training on HR management principles applied to stunting mitigation. The activity was conducted using a participatory lecture method supplemented by discussion and question-and-answer sessions. Pre-test and post-test evaluations were administered to measure improvements in participants' knowledge. Results indicated a significant increase in participants' understanding of HR management concepts—including planning, recruitment, training, and performance evaluation—as applied to stunting intervention programs. The mean pre-test score was 58.3, which increased to 82.7 after the intervention (improvement of 41.8%). These findings underscore the importance of HR management capacity-building for cadres as a foundational strategy for achieving optimal stunting reduction outcomes at the community level.